Knowledge, Attitude And Practices Regarding Personal Hygiene Of Food Handlers In Kuala Lumpur, Malaysia: A Pilot Study - Shalinawati Ramli; Nurul Azmawati Mohamed; Tengku Zetty Maztura Tengku Jamaludin2; Che Ilina Che Isahak; Nooriah Mohamed Salleh; Wan Shahida Wan Sulaiman (2024)
Non-Indexed Publication